2014
DOI: 10.2190/ec.51.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic Practices in Using Podcasting and Blogging as Teaching Tools for Teachers Seeking Esol Certificate

Abstract: Rapid globalization and the emergence of new instructional technologies have encouraged educators to explore technologies like podcasting and blogging to enhance their teaching. This study examines how six English speakers of other languages (ESOL) teachers used podcasting and blogging to help young English learners, themselves 21st century digital citizens. The ESOL teachers used technology to develop innovative teaching methods and enhance their professional identities. Four themes emerged from the examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In fact, the factor of interactive dialog and peer collaboration is related to the nature of AFL as a knowledge-construction process involving interactive dialog [75]. This result addressed this gap and was consistent with previous studies that showed that students who had the opportunity to experience dialogic teaching and learning through peer interaction were often active participants in the classroom [76][77][78]. It means that mathematics teachers and institutional administrators could give their students more opportunities to discuss theorems and propositions through interaction and collaboration.…”
Section: Discussionsupporting
confidence: 84%
“…In fact, the factor of interactive dialog and peer collaboration is related to the nature of AFL as a knowledge-construction process involving interactive dialog [75]. This result addressed this gap and was consistent with previous studies that showed that students who had the opportunity to experience dialogic teaching and learning through peer interaction were often active participants in the classroom [76][77][78]. It means that mathematics teachers and institutional administrators could give their students more opportunities to discuss theorems and propositions through interaction and collaboration.…”
Section: Discussionsupporting
confidence: 84%
“…Technology brings learners together for web-enabled interactions, provides innovative learning platforms, and offers many new ways to encounter other cultures and languages. I have done substantial research on the affordances of social media and other technologies for language learning (Fisher & Kim, 2013; Kim, 2011; Kim & Blankenship, 2013; Kim & Jang, 2014; Kim & King, 2011; Kim et al, 2018; Wang & Kim, 2014), as have many others (e.g., Belz & Thorne, 2006; Levy, 2007). We now have significant evidence that new media technologies allow learners not only to process but also to practice culturally appropriate speech and interaction autonomously and at an accelerated rate (Sercu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Publications in the sample typically used one or more existing Web 2.0 technologies, particularly social media to support students with familiar platforms, often along with other technologies, to promote communication, teacher-to-student and peer-to-peer resource sharing, collaboration, peer feedback and inquiry. Platforms included Facebook (Salmon et al, 2015), podcasting (Kim & Jang, 2014), Twitter (Marin et al, 2014), WeChat (Dai et al, 2018), WhatsApp (Willemse et al, 2019), webcasting (Freguia, 2017), wikis (Guinau Sellés et al, 2017) and YouTube (Cobley & Steven, 2014). In contrast, McCarthy (2015) developed the Café, a custom learning environment within Facebook, to better leverage its capabilities.…”
Section: Web 20mentioning
confidence: 99%